2008
DOI: 10.1021/ie071250s
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Nanomaterial Waste Soot to Recycled Sc2O3 Feedstock for the Synthesis of Metallic Nitride Fullerenes

Abstract: Herein, we address a need in the industrial and academic communities to reduce costs and environmental impact associated with the synthesis of select carbonaceous nanomaterials. In this effort, we have developed a method to recover Sc2O3 from carbonaceous “waste soot”, thereby alleviating the problem of waste disposal of fullerene depleted soot and tremendously reducing the costs and environmental impact of our synthetic process. The recovery process is based on the thermal oxidation and removal of carbon from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Yields from this process are generally low; a recent study by Stevenson et al , reported that 1000 g of feedstock were required to generate 1 g of final metallofullerene product, with the remaining ∼999 g of feedstock discarded as solid waste (or “waste soot”). On a mass basis, this solid waste fraction may be comprised of ∼50% feedstock metals, some of which are commercially valuable (e.g., rare-earth metals) or toxic in environmental systems (e.g., Cu), and thus recent efforts have focused on recovering and recycling these materials , . This unexplored area of nanotechnology EHS poses significant challenges for public health officials, waste management authorities, and generators of nanomanufacturing wastes.…”
Section: Resultsmentioning
confidence: 99%
“…Yields from this process are generally low; a recent study by Stevenson et al , reported that 1000 g of feedstock were required to generate 1 g of final metallofullerene product, with the remaining ∼999 g of feedstock discarded as solid waste (or “waste soot”). On a mass basis, this solid waste fraction may be comprised of ∼50% feedstock metals, some of which are commercially valuable (e.g., rare-earth metals) or toxic in environmental systems (e.g., Cu), and thus recent efforts have focused on recovering and recycling these materials , . This unexplored area of nanotechnology EHS poses significant challenges for public health officials, waste management authorities, and generators of nanomanufacturing wastes.…”
Section: Resultsmentioning
confidence: 99%
“…The low Sc 2 O 3 content minimizes its use, and recycling waste soot is advised. 10 At this point, we can rank the source of oxygen and its inclusion in Sc 4 (µ 3 -O) 2 @I h -C 80 as follows: NO x from copper nitrate > O 2 from air . O from Sc 2 O 3 .…”
mentioning
confidence: 99%
“…Optimal conditions for formation of Sc 4 (μ 3 -O) 2 @ I h -C 80 were an air flow of 0.2 Torr/min with graphite rods packed with 80% Cu(NO 3 ) 2 and 20% Sc 2 O 3 , which leads to a 12% yield from the soluble extract. The low Sc 2 O 3 content minimizes its use, and recycling waste soot is advised . At this point, we can rank the source of oxygen and its inclusion in Sc 4 (μ 3 -O) 2 @ I h -C 80 as follows: NO x from copper nitrate > O 2 from air ≫ O from Sc 2 O 3 .…”
mentioning
confidence: 99%
“…For the synthesis of scandium carbide endohedrals (e.g., Sc 4 C 2 @I h -C 80 ), an atmosphere deficient in air was used. For scandium carbide soot extracts, cored graphite rods were packed with Sc 2 O 3 or recycled , Sc 2 O 3 and Cu and vaporized under an inert atmosphere (e.g., He).…”
Section: Methodsmentioning
confidence: 99%